METHODS OF PREVENTION OF EARLY GESTATION COMPLICATIONS IN WOMEN WITH CHRONIC GASTRITIS - N.M. Zherebak (Bogomolets National Medical University, 2018)
Objective: to reduce the frequency of early gestational complications in pregnant women with chronic gastritis by assessing the clinical pattern of the complications, determining risk factors and prognostic criteria for their development, and introducing a two-stage prevention algorithm Material and methods. 160 pregnant women at 8-12 weeks of gestation were observed. They were divided into 3 groups: Group 1 - 58 pregnant women with chronic gastritis and early gestational complications; Group 2 - 62 pregnant women without chronic gastritis, but with early gestational complications; Group 3 - healthy pregnant women without chronic gastritis and gestational complications. In addition to the standard clinical and laboratory examination of patients, the levels of progesterone, estradiol and serum human chorionic gonadotropin (hCG) were determined by ELISA. H.pylory was diagnosed using a non-invasive method of rapid chromatographic immunoassay for the qualitative detection of IgG antibodies to H.pylory infection in serum. The acidity of gastric juice was determined by the level of gastrin 17 (G-17) in blood serum samples (S-G-17) using ELISA. Statistical analysis of the results was carried out using MedStat package. The mean value and the standard deviation of the parameter were calculated to present quantitative characters, and analysis of variance was used for comparison between groups. The frequency (%) was calculated to present qualitative characters. The chi-square test was used for the frequency in groups. The Bonferroni correction was used for pair comparison for three or more groups. The critical level of significance is assumed to be 0.05. Study results. Group 1: emesis gravidarum in 29.3%, threatened abortion in 60.3%, spontaneous miscarriage in 5.2%, missed abortion in 5.2% were diagnosed. Group 2: emesis gravidarum in 29.0%, threatened abortion in 51.6%, spontaneous miscarriage in 8.1%, missed abortion in 11.3% were diagnosed. The results of the hormonal profile study showed that in pregnant women of Group 1, the average levels of estradiol and progesterone were lower and hCG was higher than in pregnant women of Group 2, indicating a diverse change in hormonal balance that may cause early gestational complications. It is established that the frequency of emesis gravidarum, threatened abortion and spontaneous miscarriage is higher in pregnant women with chronic gastritis associated with increased basal gastric acidity with H.pylory infection. The relationship between the clinical course of gestational complications and the manifestation of chronic gastritis (vomiting, constipation) of various types, which increase the manifestations of gestational complications and determine its consequences, has been established. Based on prognostic criteria for the risk of gestational complications in pregnant women with various types of chronic gastritis, a prevention algorithm at the pregravid and gestational stages has been developed to prevent their implementation. Conclusion. The proposed two-step algorithm for diagnostic, therapeutic, and organizational measures provides a systematic approach to reduce early gestational complications in pregnant women with chronic gastritis.